Society: Solutions for Building Ethics Communication on Social Media - Andhika Tiara (Winaya Inspirasi Nusantara Foundation, 2022)
This paper discusses the values of humanism that should be applied in communication ethics in social media. One of the problems in using social media is the erosion of one's humanity. Dehumanization opens the possibility of a greater humanitarian crisis, indifference to others, even at a certain point considering others as half human, this is the beginning of a terrible humanitarian catastrophe. The Quran itself emphasizes many terms related to humanism, such as the terms al-basyar, an-nas, bani adam and alinsan. Communication in social media should aim to serve the truth and uphold human values that have begun to fade in the midst of various problems, and be able to lead humans to the perfection and completeness of a humanist society. As God exalts the human degree by mentioning various concepts in the Koran.